Small Transversal Vibrations of Elastic Rod with Point Mass at One End Subject to Viscous Friction - Gorokhova, I.V. (Журнал математической физики, анализа, геометрии, 2009)
A spectral problem describing small transversal vibrations of an elastic rod with a concentrated mass (bead) at the right end subject to viscous friction is considered. The left end is hinge-jointed. The location of the spectrum of this problem is described and the asymptotic formula of the eigenvalues is obtained.